PUBLIC CONSCIOUSNESS AS A COMPONENT FORMATION OF PROFESSIONAL VALUES OF STUDENT UNIVERSITY STUDENTS - Kopylova О.М. (Pedagogy of Higher and Secondary Education, 2022)
The article is discovered content of the concept „civic consciousness” is defined the criterions and levels its forming. The initial level this quality is defined at students of the pedagogical university and correlation between the level forming of the civis consciousness and professional values of the future teacher.